Limits on neutrino emission from gamma-ray bursts with the 40 string IceCube detector. - Abbasi, R; Abdou, Y; Abu-Zayyad, T; Adams, J; Aguilar, J; Ahlers, M; Andeen, K; Auffenberg, J; Bai, X; Baker, M; Barwick, S; Bay, R; et al. (2011)
IceCube has become the first neutrino telescope with a sensitivity below the TeV neutrino flux predicted from gamma-ray bursts if gamma-ray bursts are responsible for the observed cosmic-ray flux above 10(18)  eV. Two separate analyses using the half-complete IceCube detector, one a dedicated search for neutrinos from pγ interactions in the prompt phase of the gamma-ray burst fireball and the other a generic search for any neutrino emission from these sources over a wide range of energies and emission times, produced no evidence for neutrino emission, excluding prevailing models at 90% confidence.